Association of Digoxin Use With Transplant‐Free Interstage Survival in Infants Palliated With a Stage 1 Hybrid Procedure - Reshma K. Reddy; Sinai C. Zyblewski; Shahryar M. Chowdhury; Justin Godown; Scott M. Bradley; David W. Brown; Rachel K. Duncan; Tyler N. Brown; Katherine E. Bates; L. LuAnn Minich; John M. Costello (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Digoxin prescription in patients with single‐ventricle physiology after stage 1 palliation is associated with reduced interstage death. Prior literature has primarily included patients having undergone the Norwood procedure. We sought to determine if digoxin prescription at discharge in infants following hybrid stage 1 palliation was associated with improved transplant‐free interstage survival. Methods and Results A retrospective multicenter cohort analysis was conducted using data from the National Pediatric Cardiology Quality Improvement Collaborative registry data from 2008 to 2021. Infants with functional single ventricles and aortic arch obstruction discharged home after the hybrid stage 1 palliation hospitalization were included. Patients were excluded if they had supraventricular tachycardia or conversion to Norwood operation. The primary outcome was transplant‐free survival. Multivariable logistic regression analysis including a propensity score for digoxin use identified associations between digoxin use and interstage death or transplant. Of 259 included infants from 45 sites, 158 (61%) had hypoplastic left heart syndrome. Forty‐nine percent had a gestational age ≤38 weeks, 18% had a birth weight <2.5 kg, and 58% had a preoperative risk factor. Of the 259 subjects, 129 (50%) were discharged on digoxin. Interstage death or transplant occurred in 30 (23%) patients in the no‐digoxin group compared with 18 (14%) in the digoxin group (P=0.06). With multivariate analysis, discharge digoxin prescription was associated with a lower risk of interstage death or transplant (adjusted odds ratio, 0.48 [95% CI, 0.24–0.93]; P=0.03). Conclusions In infants with single‐ventricle physiology who underwent hybrid stage 1 palliation, digoxin prescription at hospital discharge was associated with improved interstage transplant‐free survival.